A sirolimus-eluting bioabsorbable polymer-coated stent (MiStent) versus an everolimus-eluting durable polymer stent (Xience) after percutaneous coronary intervention (DESSOLVE III): a randomised, single-blind, multicentre, non-inferiority, phase 3 trial. Issue 10119 (3rd February 2018) - de Winter, Robbert J; Katagiri, Yuki; Asano, Taku; Milewski, Krzysztof P; Lurz, Philipp; Buszman, Pawel; Jessurun, Gillian A J; Koch, Karel T; Troquay, Roland P T; Hamer, Bas J B; Ophuis, Ton Oude; Wöhrle, Jochen; et al.
Summary: Background: MiStent is a drug-eluting stent with a fully absorbable polymer coating containing and embedding a microcrystalline form of sirolimus into the vessel wall. It was developed to overcome the limitation of current durable polymer drug-eluting stents eluting amorphous sirolimus. The clinical effect of MiStent sirolimus-eluting stent compared with a durable polymer drug-eluting stents has not been investigated in a large randomised trial in an all-comer population. Methods: We did a randomised, single-blind, multicentre, phase 3 study (DESSOLVE III) at 20 hospitals in Germany, France, Netherlands, and Poland. Eligible participants were any patients aged at least 18 years who underwent percutaneous coronary intervention in a lesion and had a reference vessel diameter of 2·50–3·75 mm. We randomly assigned patients (1:1) to implantation of either a sirolimus-eluting bioresorbable polymer stent (MiStent) or an everolimus-eluting durable polymer stent (Xience). Randomisation was done by local investigators via web-based software with random blocks according to centre. The primary endpoint was a non-inferiority comparison of a device-oriented composite endpoint (DOCE)—cardiac death, target-vessel myocardial infarction, or clinically indicated target lesion revascularisation—between the groups at 12 months after the procedure assessed by intention-to-treat. A margin of 4·0% was defined for non-inferiority of the MiStent group compared with the Xience group. All participants were included in the safety analyses. This trial is registered with ClinicalTrials.gov, number NCT02385279 . Findings: Between March 20, and Dec 3, 2015, we randomly assigned 1398 patients with 2030 lesions; 703 patients with 1037 lesions were assigned to MiStent, of whom 697 received the index procedure, and 695 patients with 993 lesions were asssigned to Xience, of whom 690 received the index procedure. At 12 months, the primary endpoint had occurred in 40 patients (5·8%) in the sirolimus-eluting stent group and in 45 patients (6·5%) in the everolimus-eluting stent group (absolute difference −0·8% [95% CI −3·3 to 1·8], pnon-inferiority =0·0001). Procedural complications occurred in 12 patients (1·7%) in the sirolimus-eluting stent group and ten patients (1·4%) in the everolimus-eluting stent group; no clinical adverse events could be attributed to these dislodgements through a minimum of 12 months of follow-up. The rate of stent thrombosis, a safety indicator, did not differ between groups and was low in both treatment groups. Interpretation: The sirolimus-eluting bioabsorbable polymer stent was non-inferior to the everolimus-eluting durable polymer stent for a device-oriented composite clinical endpoint at 12 months in an all-comer population. MiStent seems a reasonable alternative to other stents in clinical practice. Funding: The European Cardiovascular Research Institute, Micell Technologies (Durham, NC, USA), and Stentys (Paris, France).